2015
DOI: 10.1111/odi.12381
|View full text |Cite
|
Sign up to set email alerts
|

New bone formation induced by surface strontium‐modified ceramic bone graft substitute

Abstract: These results suggest that the surface Sr modification by wet chemical treatment is a promising approach to enhance the early bone healing capacity of osteoconductive ceramic bone substitutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In dentistry, bone loss may occur in tooth extractions, oncological rejections, fractures, and traumas 1 . Dental implant placement is one of the most frequent situations where bone volume augmentation is needed 2,3 . The current gold standard technique for bone regeneration is the use of autologous graft, which may create morbidity for the donor and has a limitation in the bone volume that can be donated 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In dentistry, bone loss may occur in tooth extractions, oncological rejections, fractures, and traumas 1 . Dental implant placement is one of the most frequent situations where bone volume augmentation is needed 2,3 . The current gold standard technique for bone regeneration is the use of autologous graft, which may create morbidity for the donor and has a limitation in the bone volume that can be donated 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Also Park et al, demonstrated that strontium modified ceramic bone graft substitute showed early osteoblast differentiation. ALP activity, OC, transcriptional factors like Runx2 and Osterix was found to be upregulated comparing with other samples without Sr (33). Moreover, presence of Sr ions can interact and down regulate release of proinflammatory cytokine like TNF-α (tumor necrosis factor α) and IL-1 (interleukin 1) (14).…”
Section: Expression Changes Of Bone Biomarkersmentioning
confidence: 93%
“…Many studies have been investigating Sr effects in different biomaterials and results are encouraging. Strontium ions are being incorporated in different biomaterials and metallic implants like synthetic hydroxyapatites, glass ceramics, bioactive glasses, calcium phosphate cements or metallic implants with different alloys, searching for increased bone quality and formation in bone tissue defects or around osseointegrating implants (22,25,29,33,52). In recent years there is a development of injectable materials for filling bone defects as minimally invasive techniques.…”
Section: Strontium and Biomaterialsmentioning
confidence: 99%
“…The local use of strontium for promoting bone growth usually involves the incorporation of strontium into bone grafts [ 20 , 21 , 22 ]. Other strontium delivery methods include strontium associated with collagen sponge [ 23 ], strontium-containing collagen membrane and strontium dissolved in gel [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%